Materials and sustainable development - Ashby, M. F. (Butterworth-Heinemann, 2016)
This title provides a structure and framework for analysing sustainable development and the role of materials in it. The aim is to introduce ways of exploring sustainable development to readers in a way that avoids simplistic interpretations and approaches complexity in a systematic way.